Where the thoughts dwell: history of neuroscience and introduction into neuroglia - Verkhratsky, Alexei (Henry Stewart Talks, 2011)
Where the thoughts dwell, Cortical localisation of functions, The cellular theory, Images of neural cells, The glia, Neuroglia, Glial cell distribution, Evolution of neuroglia, Evolution of glial function, Microglia